2021
DOI: 10.1016/j.cjco.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Social Media as a Tool to Advance Women in Cardiology: Paving the Way for Gender Equality and Diversity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…3 It has been reported that social media plays a vital role in advancing diversity in health professions, providing peer-to-peer support among members of minority groups, fostering mentorship and professional development, recognizing accomplishments, and promoting empowerment. 23,24 Professional sonography organizations could develop strategies to solicit funds from government, corporate, and commercial institutions to promote sonography as a profession to diverse minority communities. Professional organizations such as the National Medical Association, National Dental Association, National Hispanic Medical Association, The Hispanic Doctors & Chiropractic Association, National Black Nurses Association, and Asian American Pacific Islander Nurses Association have established practices that promote the profession to minority communities, represent interests of minority groups, and work on establishing a professional presence at legislative levels.…”
Section: Discussionmentioning
confidence: 99%
“…3 It has been reported that social media plays a vital role in advancing diversity in health professions, providing peer-to-peer support among members of minority groups, fostering mentorship and professional development, recognizing accomplishments, and promoting empowerment. 23,24 Professional sonography organizations could develop strategies to solicit funds from government, corporate, and commercial institutions to promote sonography as a profession to diverse minority communities. Professional organizations such as the National Medical Association, National Dental Association, National Hispanic Medical Association, The Hispanic Doctors & Chiropractic Association, National Black Nurses Association, and Asian American Pacific Islander Nurses Association have established practices that promote the profession to minority communities, represent interests of minority groups, and work on establishing a professional presence at legislative levels.…”
Section: Discussionmentioning
confidence: 99%
“…The power of social media can be harnessed to promote crowdsourcing in a goal directed manner for this purpose as reflected in the social media campaigns #NYerORCover Challenge launched by Dr. Susan Pitt and #ILookLikeASurgeon set in motion by Dr. Heather Logghe ( 22 ). The connectivity supplied by social media can also promote opportunities for FIT and/or early career women to join peer support groups or engage in a wider range of professional networking ( 23 , 24 ). Such methods of encouragement and inclusivity are also being practiced outside of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers are especially jarring as women make up just under half of Internal Medicine residents [86]. Notably, this disparity is also seen in healthcare system leadership positions and roles on journal editorial boards [25,[87][88][89]. This gap is further pronounced in cardiologists of minority backgrounds, with more than half of cardiologists in the USA being White, 3% Black, and 4.2% Hispanic or Latino [90][91][92].…”
Section: Women In Cardiology (Wic)mentioning
confidence: 99%